A Fully 3D‐Printed Wearable Piezoresistive Strain and Tactile Sensing Array for Robot Hand. Issue 7 (28th May 2021) - Pei, Zhen; Zhang, Qiang; Yang, Kun; Yuan, Zhongyun; Zhang, Wendong; Sang, Shengbo
Abstract: The wide application prospects of flexible strain sensors and pressure sensors in robotic perception have led to an urgent demand for the high‐precision customized manufacturing and flexible integration of such devices. Herein, a 3D‐printed wearable strain and tactile sensing array is developed for robotic perception by integrating a flexible strain sensor and a pressure sensor with porous structures. The flexible strain sensor has a wide linear measurement range of 67.5% with a sensitivity of 2.64. Meanwhile, the flexible pressure sensor has a continuous pressure‐monitoring ability in the range of 0–1 N, and it is particularly sensitive to small pressures within 0.2 N. Both the sensors provide a stable output for the seamless sensing of different stimuli, and devices from the same batch provide highly consistent responses. By fully exploiting the flexibility of digital light‐processing 3D printing, the sensing array is customized for a robotic hand to realize the grip and finger bending perceptions of the manipulator. Abstract : Patterned porous structures significantly enhance the sensing performance of flexible strain sensors and pressure sensors. The consistency between sensor devices is improved by 3D printing, which also realizes easy adjustment of sensor design. Integrating these flexible strain sensors and pressure sensors, a 3D‐printed flexible sensing array can impart the robot hand with sensing ability of grasp and tactile.